Responding to Bad Press: How CEO Temporal Focus Influences the Sensitivity to Negative Media Coverage of Acquisitions - Gamache, Daniel L.; McNamara, Gerry (Academy of Management Journal, 2019)
Management scholars have demonstrated that CEOs look to cues provided from external stakeholders when determining the direction and timing of strategic action. Research has focused on “hard” forms of external performance feedback, primarily in the form of stock market reactions. To understand both whether and to what degree “soft” external performance feedback of strategic actions influences the subsequent strategic decisions of firms, we build our arguments from and contribute to upper echelons theory. We argue that negative media reactions to the announcement of a major acquisition will shape the degree to which the firm will engage in subsequent acquisition activity. However, our theory suggests that an important individual attribute, CEO temporal focus, will influence how sensitive CEOs are to media coverage. Using a sample of 747 large acquisitions made between 2006 and 2011, we find strong support for our hypotheses. Additionally, our supplemental analysis demonstrates an important difference between the influence of stock market and media reactions following an acquisition. While CEO temporal focus shapes which CEOs will be influenced by media reactions, it appears that CEOs’ propensity to be influenced by stock market reactions is not moderated by their temporal focus.